Investigation and characterization by TG/DTG–DTA and DSC of the fusion of Riboflavin, and its interaction with the antibiotic norfloxacin in the screening of cocrystal - Ferreira, Laura Teófilo [UNESP]; Alarcon, Rafael Turra [UNESP]; Perpétuo, Glauco Lini [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2018)
This work synthesized and characterized the NOR-RIB 1:1 (mol–mol) cocrystal. During a study of the reagents, Riboflavin (RIB) melted at 304 °C, which is different from the temperature previously reported in the literature (280–290 °C); therefore, this compound was characterized individually. Subsequently, the cocrystal was synthesized with the active pharmaceutical ingredient (API) norfloxacin (NOR) with the RIB coformer, and the mechanochemical synthesis route was adopted. NOR, RIB, and the cocrystal were characterized by thermogravimetry–differential thermal analysis (TG–DTA), differential scanning calorimetry (DSC), DSC coupled to a microscope (photo-DSC), mid-infrared spectroscopy (MIR), and powder X-ray diffraction. The results of thermal analysis showed that the RIB starts decomposition process (260 °C) and then melts (304 °C). The MIR found that beginning at 295 °C, the RIB passes into the form of a decomposition intermediate; therefore, the melting point observed in the DSC curve is related to this decomposition material. The cocrystal presented thermal stability (200 °C) lower than the API (235 °C) and the coformer (260 °C). The DSC curve did not contain a melting peak. The bands at 1726 cm−1 (C=O of the carboxylic acid) for the NOR, and the band at 3326 cm−1 (stretch O–H), among others, were not visible for the cocrystal in the MIR spectrum, indicating interactions in these regions. The X-ray diffractograms showed a new diffraction pattern, which proved the obtainment of a new phase and cocrystal formation.
Keywords: Cocrystal; Mechanochemistry; Norfloxacin; Photo-DSC; Riboflavin; TG–DTA